Phenotype, Susceptibility, Autoimmunity, and Immunotherapy Between Kawasaki Disease and Coronavirus Disease-19 Associated Multisystem Inflammatory Syndrome in Children - Chen, Ming-Ren; Kuo, Ho-Chang; Lee, Yann-Jinn; Chi, Hsin; Li, Sung Chou; Lee, Hung-Chang; Yang, Kuender D. (Frontiers in Immunology, 2021)
Coronavirus disease-19 (COVID-19) in children is usually mild but some are susceptible to a Kawasaki disease (KD)-like multisystem inflammatory syndrome in children (MIS-C) in the convalescent stage, posing a need to differentiate the phenotype, susceptibility, autoimmunity, and immunotherapy between KD and MIS-C, particularly in the upcoming mass vaccination of COVID-19. Patients with MIS-C are prone to gastrointestinal symptoms, coagulopathy, and shock in addition to atypical KD syndrome with fever, mucocutaneous lesions, lymphadenopathy, and/or cardiovascular events. MIS-C manifests KD-like symptoms that alert physicians to early recognize and adopt the KD treatment regimen for patients with MIS-C. MIS-C linked to COVID-19 teaches us infection-associated autoimmune vasculitis and vice versa. Studies on genetic susceptibility have identified certain human leukocyte antigen (HLA) locus and toll-like receptor (TLR) associated with KD and/or COVID-19. Certain HLA subtypes, such as HLA-DRB1 and HLA-MICA A4 are associated with KD. HLA-B*46:01 is proposed to be the risk allele of severe COVID-19 infection, and blood group O type is a protective factor of COVID-19. The autoimmune vasculitis of KD, KD shock syndrome (KDSS), or MIS-C is mediated by a genetic variant of HLA, FcγR, and/or antibody-dependent enhancement (ADE) resulting in hyperinflammation with T helper 17 (Th17)/Treg imbalance with augmented Th17/Th1 mediators: interleukin-6 (IL-6), IL-10, inducible protein-10 (IP-10), Interferon (IFNγ), and IL-17A, and lower expression of Treg-signaling molecules, FoxP3, and transforming growth factor (TGF-β). There are certain similarities and differences in phenotypes, susceptibility, and pathogenesis of KD, KDSS, and MIS-C, by which a physician can make early protection, prevention, and precision treatment of the diseases. The evolution of immunotherapies for the diseases has shown that intravenous immunoglobulin (IVIG) alone or combined with corticosteroids is the standard treatment for KD, KDSS, and MIS-C. However, a certain portion of patients who revealed a treatment resistance to IVIG or IVIG plus corticosteroids, posing a need to early identify the immunopathogenesis, to protect hosts with genetic susceptibility, and to combat Th17/Treg imbalance by anti-cytokine or pro-Treg for reversal of the hyperinflammation and IVIG resistance. Based on physiological and pathological immunity of the diseases under genetic susceptibility and host milieu conditions, a series of sequential regimens are provided to develop a so-called “Know thyself, enemy (pathogen), and ever-victorious” strategy for the prevention and immunotherapy of KD and/or MIS-C.